Comparison of conventional immunosuppressive drugs versus anti-TNF-α agents in non-infectious non-anterior uveitis. Issue 113 (September 2020) - Leclercq, Mathilde; Langlois, Vincent; Girszyn, Nicolas; Le Besnerais, Maëlle; Benhamou, Ygal; Levesque, Hervé; Muraine, Marc; Gueudry, Julie
Abstract: Objective: To compare the efficacy and safety of Disease-modifying antirheumatic drugs (DMARDs) and anti-TNF-α agents in patients with non-infectious non-anterior uveitis. Methods: Single center retrospective study including adult patients with non-infectious intermediate, posterior or pan-uveitis. Outcomes were compared between patients treated with DMARDs or anti-TNF-α agents. The primary outcome was treatment failure or occurrence of serious adverse events. Treatment failure was determined by ophthalmologic criteria. Results: Seventy-three patients were included, mostly female (52%). Among them, 39 were treated with DMARDs and 34 with anti-TNF-α agents. The main uveitis causes were idiopathic (30%), birdshot chorio-retinopathy (25%), sarcoidosis (16%) and Behçet's disease (14%). The primary outcome was observed in 56% of patients treated with anti-TNF-α agents versus 59% of patients treated with DMARDs (p = 0.82). Median time to observe the primary outcome was 16 months (anti-TNF-α group) versus 21 months (p = 0.52). There was no significant difference between the two groups in terms of treatment failure, corticosteroid sparing effect, visual acuity improvement or adverse events. Earlier control of ocular inflammation was achieved with anti-TNF-α agents than with DMARDs (p = 0.006). In relapsing patients, anti-TNF-α agents allowed better corticosteroid sparing (p = 0.06). Conclusion: DMARDs could still be used as first-line therapy for non-infectious non-anterior uveitis after corticosteroid therapy. However, anti-TNF-α agents could be proposed as an alternative in cases of severe inflammation or initial high level of steroid dependency. Highlights: The rate and median time to observe primary outcome were not statistically different between anti-TNF-α agents and DMARDs. There was no significant difference in terms of visual acuity improvement or adverse events between the two groups. In relapsing patients, anti-TNF-α agents allowed better corticosteroid sparing.